2011
DOI: 10.1007/s10126-011-9416-1
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Polyhydroxyalkanaotes by a Novel Facultatively Anaerobic Vibrio sp. under Marine Conditions

Abstract: Marine bacteria have recently attracted attention as potentially useful candidates for the production of practical materials from marine ecosystems, including the oceanic carbon dioxide cycle. The advantages of using marine bacteria for the biosynthesis of poly(hydroxyalkanoate) (PHA), one of the eco-friendly bioplastics, include avoiding contamination with bacteria that lack salt-water resistance, ability to use filtered seawater as a culture medium, and the potential for extracellular production of PHA, all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 43 publications
(42 reference statements)
0
33
0
Order By: Relevance
“…In this regard, there are many reports of the use of terrestrial bacteria for bioplastic production. [27][28][29][30][31] However, the reports are scanty from the marine environment sources. 32) In comparison to terrestrial environment, marine sources are the less explored environmental conditions for the microbial diversity as well as the screening of potential marine bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, there are many reports of the use of terrestrial bacteria for bioplastic production. [27][28][29][30][31] However, the reports are scanty from the marine environment sources. 32) In comparison to terrestrial environment, marine sources are the less explored environmental conditions for the microbial diversity as well as the screening of potential marine bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Lee and coworkers reported that the reduction in dissolved oxygen concentration from 40% to 5% inhibited cell growth of recombinant Escherichia coli harboring PHA-synthesis genes and enhanced PHA contents from 10 to 27 wt% (21), demonstrating that PHA production could be enhanced under conditions similar to the aerobic-anaerobic ones used here. In our study, the strain cultured under the aerobic-anaerobic condition demonstrated constant cell growth irrespective of whether glucose, fructose or gluconate was used as the sole carbon source ( Table 2) (20). Here, an aerobic-anaerobic condition denotes that the strain was prepared and sealed under nitrogen atmosphere and cultured.…”
Section: Pha Production Using Sugars and Organic Acidmentioning
confidence: 99%
“…KN01, was investigated with respect to PHA productivity from well-known carbon sources, namely, glucose, fructose or gluconate at 30°C for 48 h under an aerobic condition (Table 2) (20). The strain exhibited cell growth ranging from approximately 1.4 to 1.7 g/L.…”
Section: Pha Production Using Sugars and Organic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Only Vibrio sp. KN01 was able to synthesize the terpolymer consisting of 14 mol% 3HP, 83 mol% 3HB, and 3 mol% 5HV from soybean oil (productivity [P PHA ], 3.3 mg PHA liter Ϫ1 h Ϫ1 ) under aerobic or anaerobic conditions (46).…”
Section: Hp-containing Ter-and Tetrapolymersmentioning
confidence: 99%